Mesenchymal Stem Cell Therapy - Chase, Lucas G.; Chase, Lucas G.; Vemuri, Mohan C.; Vemuri, Mohan C. (Stem Cell Biology and Regenerative Medicine,, 2013)
Mesenchymal Stem Cells or Multipotent Mesenchymal Stromal Cells (collectively referred to as MSCs) are currently being tested in a number of clinical trials for various diseases including graft-versus-host disease, Crohn’s disease, myocardial infarction, stroke, diabetes, cartilage defects, and many others. The increasing number of clinical trials globally indicates the likely therapeutic potential of this specialized adult stem cell.  Over the last decade, there has been tremendous progress towards understanding an MSC’s phenotype, expansion features in culture, differentiation ability and global gene and protein expression profiles.  Despite the enormous progress and data accrual at the molecular and cellular levels, several questions remain as to the utility of MSCs for clinical applications.    Mesenchymal Stem Cell Therapy is a comprehensive collection of information comprised of both basic and pre-clinical biological studies as well as current advances in clinical applications within the MSC therapy field.  This text is a resource for both the basic life science and cell therapy researchers and includes a spectrum of review chapters from top experts in the field discussing clinical scale culture, regulatory issues, genetic engineering, disease specific applications and others.